Significance of diagnostic laparoscopy and determination of free cancer cells in peritoneal lavage fluid in patients with gastric carcinoma - Perišić Nenad; Kostić Zoran; Doder Radoje; Brčerević Irina; Petrović Stanko; Slavković Damjan (Vojnosanitetski Pregled)
nema